Pendampingan Ibu Hamil Di Lokus Stunting Wilayah Yogyakarta - Syagata, Anindhita; Fayakun Nur Rohmah; Esitra Herfanda; Dittasari Putriana; Teti Anggita Safitri (ABDIMAS Madani, 2023)
Stunting is a nutritional problem in Indonesia, and there are 10 stunting loci in Sleman Regency, Yogyakarta, one of which is Sendangmulyo Village. Early stunting develops in the womb, so the nutritional status of pregnant women is important to pay attention to. Pregnant women who have a chronic lack of energy have a higher risk of giving birth to malnourished children. The stunting rate is still high, and stakeholders focus on handling children, even though it can also be seen in nutrition during pregnancy. The goal of this community service is to provide education to increase knowledge and to monitor and assist pregnant women with their nutrition and health. A total of seven pregnant women became respondents to this activity and were accompanied for one month in September 2022. Prior to the mentoring, nutrition education was provided on August 9, 2022. The result of the educational activity was an increase in knowledge among the respondents; for example, only two pregnant women received nutrition education and managed their diets well. From both, there was an improvement in nutritional consumption and food variety.